The Mouse Clock Locus: Sequence and Comparative Analysis of 204 Kb from Mouse Chromosome 5 - Wilsbacher, Lisa D.; Sangoram, Ashvin M.; Antoch, Marina P.; Takahashi, Joseph S. (Genome Research, 2000)
The Clock gene encodes a basic helix-loop-helix (bHLH)–PAS transcription factor that regulates circadian rhythms in mice. We previously cloned Clock in mouse and human using a battery of behavioral and molecular techniques, including shotgun sequencing of two bacterial artificial chromosome (BAC) clones. Here we report the finished sequence of a 204-kb region from mouse chromosome 5. This region contains the complete loci for the Clock andTpardl (pFT27) genes, as well as the 3′ partial locus of the Neuromedin U gene; sequence analysis also suggests the presence of two previously unidentified genes. In addition, we provide a comparative genomic sequence analysis with the syntenic region from human chromosome 4. Finally, a new BAC transgenic line indicates that the genomic region that is sufficient for rescue of the Clock mutant phenotype is no greater than 120 kb and tightly flanks the 3′ end of the Clockgene.[The sequence data reported in this paper have been submitted to the GenBank data library under accession no. AF146793.]
10.1101/gr.155400